Consultation-liaison psychiatry in situations of crisis: the casse of the COVID-19 pandemic - Huarcaya-Victoria, Jeff (2025)
The COVID-19 pandemic has severely challenged public health at a global level, profoundly affecting Peru and underscoring the need to address both physical and mental health during health crises. Consultation liaison psychiatry, specialized in integrating psychiatry with general medicine, has emerged as a crucial discipline in the management of psychiatric complexities, exacerbated during the pandemic. Liaison psychiatrists have played a vital role in identifying and treating psychiatric manifestations among hospitalized patients, as well as providing emotional support to healthcare personnel. Strategies such as early consultation and the use of standardized assessment tools have facilitated early detection and effective management ofconditions such as depression and anxiety. Additionally, an innovative use of telepsychiatry has enabled continuity of care during social distancing. However, the pandemic has also highlighted significant challenges, including additional stress among healthcare workers and the need of adequate resources in Intensive Care Units. Strengthening training in consultation liaison psychiatry and improving infrastructure are crucial steps for the management of future health emergencies. This article underscores the importance of integrating psychiatric care in the global response to pandemics, thereby enhancing the health system's resilience and the patients' clinical outcomes.